Younger patients with Waldenström Macroglobulinemia exhibit low risk profile and excellent outcomes in the era of immunotherapy and targeted therapies. Issue 12 (9th September 2020) - Varettoni, Marzia; Ferrari, Angela; Frustaci, Anna M.; Ferretti, Virginia V.; Rizzi, Rita; Motta, Marina; Piazza, Francesco; Merli, Michele; Benevolo, Giulia; Visco, Carlo; Laurenti, Luca; Ferrero, Simone; et al.
Abstract: We analyzed 160 young Waldenström Macroglobulinemia (WM) patients with a median age of 49 years (range 23‐55 years), diagnosed between January 2000 and January 2019 in 14 Italian centers. At diagnosis, 70% of patients were asymptomatic. With a median follow‐up of 5.6 years, 57% have been treated. As initial therapy 79% of patients received chemo‐immunotherapy, 13% a chemo‐free induction and 8% chemotherapy only. At relapse or progression, 6% underwent an autologous stem cell transplantation. Overall, 19% of patients received ibrutinib during the course of the disease. According to IPSSWM, 63% were classified as low risk, 27% as intermediate risk and 10% as high risk. Five‐year OS was shorter in high‐risk as compared with low or intermediate risk patients (92.9% vs 100% P = .002). According to revised IPSSWM, 92% were classified as very low or low risk and 8% as intermediate risk, with a shorter 5‐year OS in the latter group (87.5% vs 100%, P = .028). The OS of young WM patients was not significantly reduced as compared with age‐matched, sex‐matched and calendar year‐matched general population. Early diagnosis, absence of high‐risk features in symptomatic patients and high efficacy of modern treatments are the main determinants of the excellent outcome of young WM patients.